Psychological Toll of the COVID-19 Pandemic: An In-Depth Exploration of Anxiety, Depression, and Insomnia and the Influence of Quarantine Measures on Daily Life - Aljaberi M.A.; Al-Sharafi M.A.; Uzir M.U.H.; Sabah A.; Ali A.M.; Lee K.-H.; Alsalahi A.; Noman S.; Lin C.-Y. (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
The COVID-19 pandemic, on a global scale, has prompted multifaceted challenges, including a notable psychological toll on the general population. This study uses mixed-method approach for a nuanced exploration of these experiences. Using a phenomenological strategy, qualitative responses from 999 participants were analyzed regarding their pandemic-induced anxiety and the influence of quarantine measures on their lives. Quantitative measures, including the revised Impact of Event Scale (IES-R), patient health questionnaire-9 (PHQ-9), the seven-item generalized anxiety disorder assessment (GAD-7), and Insomnia Severity Index (ISI), were used to quantify trauma, depression, anxiety, and insomnia attributed to COVID-19. Partial least squares structural equation modeling (PLS-SEM) was utilized for quantitative data analysis. The anxiety-related responses were mainly clustered into four themes: life threats, support shortage, economic consequences, and disruptions to family and social life. Subthemes that addressed the perceived effects encapsulated disruptions to academic and professional lives, familial and social relationships, psychopathological stress, and movement limitations. The findings from quantitative analysis revealed the significant associations between COVID-19-related trauma and symptoms of anxiety, depression, and insomnia, as indicated by coefficients exceeding 0.10 (all z-values > 1.96